2007
DOI: 10.1051/0004-6361:20066649
|View full text |Cite
|
Sign up to set email alerts
|

Photospheric flows around a quiescent filament

Abstract: Context. The horizontal photospheric flows below and around a filament are one of the components in the formation and evolution of filaments. Few studies exist because they require multiwalength time sequences at high spatial resolution. Aims. Our objective is to measure the horizontal photospheric flows associated with the evolution and eruption of a filament. Methods. We present observations obtained in 2004 during the international JOP 178 campaign which involved eleven instruments both in space and at grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…One proposed cause of such alignment is in the relative motion of the photospheric fibril footpoints in the two different polarities (e.g., Wang and Muglach, 2007). Photospheric flux convergence is often caused by supergranular divergence motions at the sides and across the PIL (e.g., Rondi et al, 2007). Both cases studied by Wang and Muglach (2007) exhibited convergence toward the neutral line, but in the first case there was also parallel motion, while it was anti-parallel in the second case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed cause of such alignment is in the relative motion of the photospheric fibril footpoints in the two different polarities (e.g., Wang and Muglach, 2007). Photospheric flux convergence is often caused by supergranular divergence motions at the sides and across the PIL (e.g., Rondi et al, 2007). Both cases studied by Wang and Muglach (2007) exhibited convergence toward the neutral line, but in the first case there was also parallel motion, while it was anti-parallel in the second case.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sporadic minor polarity concentrations around the PIL has also been considered important for filament formation. Rondi et al (2007) claim that the converging motions may transport these small scale polarities across the PIL, thus forming the parasitic polarities in which filament barbs are thought to be rooted. They identified this process as causing the formation of the filament barbs, as supported by other observations (e.g., Schmieder et al, 2006) and modeling (e.g., Aulanier and Schmieder, 2002).…”
Section: Living Reviews In Solar Physicsmentioning
confidence: 99%
“…Photospheric converging or shearing flows may be detected by local correlation tracking (cf. Magara, 1999;Rondi et al, 2007;. For some surface models diffusion of flux towards a PIL with subsequent cancellation plays the role of the converging flow.…”
Section: Theoretical Models Of Filament Formationmentioning
confidence: 99%
“…They found a pattern in the large scale horizontal flows at the solar surface that interacts with the differential rotation. The local photospheric flows were also measured with a higher spatial resolution (0.5 arcsec) in the filament channel during its eruption phase using TRACE 1600 Å to show the coupling between convection and magnetic field (Rondi et al 2007). It was shown that the disappearance of the filament originates in a filament gap.…”
Section: Introductionmentioning
confidence: 99%